2005
DOI: 10.1002/mrm.20710
|View full text |Cite
|
Sign up to set email alerts
|

Tissue segmentation and classification of MRSI data using canonical correlation analysis

Abstract: Nowadays, MRSI represents a powerful non-invasive diagnostic tool. The ability of Magnetic Resonance Spectroscopy to detect metabolites is already very useful in daily radiologic practice since it provides significant biochemical information on the molecules of the organism under investigation. MRSI data can also be exploited in tissue segmentation techniques, which play a crucial role in many biomedical applications, such as the quantification of tissue volumes, localization of possible pathologies, improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 15 publications
0
53
0
Order By: Relevance
“…Canonical correlation analysis (CCA) is a multivariate technique often used in psychological, climate and ecological studies to quantify the associations between two separate data sets measured on the same experimental units (22)(23)(24)(25). In contrast to the aforementioned pairwise correlation analysis, CCA yielded a much stronger correlation of 0.73.…”
Section: Canonical Correlation Reveals a Close Link Between Biomass Amentioning
confidence: 99%
“…Canonical correlation analysis (CCA) is a multivariate technique often used in psychological, climate and ecological studies to quantify the associations between two separate data sets measured on the same experimental units (22)(23)(24)(25). In contrast to the aforementioned pairwise correlation analysis, CCA yielded a much stronger correlation of 0.73.…”
Section: Canonical Correlation Reveals a Close Link Between Biomass Amentioning
confidence: 99%
“…20 and 23, z score was employed for MRS based detection of glioma and CaP, respectively. Another statistical technique, canonical correlation analysis 蛻CCA蛼, 24 based on calculating the canonical coefficients to obtain correlated linear relationships between two multidimensional variables was shown to be useful in successfully classifying prostate MRSI datasets into four classes: Aggressive tumor, tumor, mixed tissue, and healthy tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, as described in the Introduction, MRSI provides biochemical information as well as spatial information about the sample under investigation and a natural assumption is that neighbour voxels contain similar tissue types. Previous studies carried out on other algorithms [41,42] already showed that the simultaneous exploitation of the two types of information significantly improves the performance of the considered methods. Hence, it is reasonable to expect similar improvements by introducing spatial information in the NMF-based algorithms as well.…”
Section: Discussionmentioning
confidence: 98%